Respon Pertumbuhan Padi Mutan Insersi pada Kondisi Nitrogen Rendah - Ade Nena Nurhasanah; Satya Nugroho (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Nurhasanah et al, 2017. Response Rice Mutant Insertion Growth in the Low Nitrogen Conditions. JLSO 6(1):49-58.Nitrogen is an essential fertilizer for growing rice because N needed higher than other nutrients. Therefore, many farmers apply a large amount of nitrogen fertilizer to obtain high production. Unfortunately, the plant not utilized much and only 50-60 % of the total N was applied which able to used. It would be lost through a combination of leaching, surface run-off, denitrification, volatilization and microbial consumption. Thus, the large amount N fertilizer application increase input cost and damage the environment. To build sustainable agriculture, the screening of varieties or mutant which is capable of using N efficiently is necessary. In addition, knowledge of N regulation and mechanisms in plants needs to be exploited for efficient plant development in the use of N. This study aims to look at the response of mutant rice plants in the low N conditions and obtain mutant rice plant candidates which is efficiently in using N. Seventen mutan insertion and Niponbare as wildtype are used in this experiment. Rice mutant plants were grown hydroponically inYoshida solution with different N concentration. Under normal conditions the N concentration was 1.14 mM/L and in the low N concentration was about 0.114 mM./L. Parameters was measured in this study were plant height, root length and dry weight. The results showed that plant height mutant insertion wasnot influenced by N concentration in nutrient solution. Meanwhile root lenght and dry weight plant parameter are affected by N consentration. There are mutant insertion plant that have potential and the optimum growth ability at low N concentration, especially B101. Validation on that mutants will be done in the next research.